The Relationship Of Students' Social Interaction With Students' Learning Interest - Murni, Sri; Zahra Bulantika, Siti; Puspita Sari, Rizka; Afifah, Atik; Fitri, Gita (Universitas Negeri Padang, 2023)
he purpose of this study was to find out whether there was a significant relationship between students' social interaction with students' learning interests and how the direction and level of closeness of students' social interaction relationship with students' learning interests in class X even semester at SMA Negeri 8 Bandar Lampung. The research method used is descriptive quantitative where in this study the authors distributed questionnaires about social interaction and interest in learning. Based on the results of the study, it can be concluded that there is a positive relationship between students' social interaction and learning interest, there is a degree of closeness of the relationship between students' social interaction and students' learning interests, there is a level of strength of social interaction in students, there is a relationship pattern between students' social interaction students with an interest in learning and there is a significant relationship between social interaction of students with interest in learning in class X students in the even semester at SMA Negeri 8 Bandar Lampung so that this research was declared acceptedKeywords: Social interaction, interest in learning